2021
DOI: 10.1002/adfm.202101378
|View full text |Cite
|
Sign up to set email alerts
|

A Moisture‐Driven Actuator Based on Polydopamine‐Modified MXene/Bacterial Cellulose Nanofiber Composite Film

Abstract: As a new 2D material, MXene (Ti 3 C 2 T x ) shows great potential as a smart multifunctional humidity-responsive actuator due to its high hydrophilicity and conductivity but suffers from ambient oxidation and mechanical brittleness. Inspired by the mussels, the authors overcome these weaknesses by designing and fabricating a nacre-like and lamellar-structured composite film that consists of polydopamine-modified MXene and bacterial cellulose nanofibers, which shows improved properties as a moisture-driven actu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
141
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(159 citation statements)
references
References 46 publications
(9 reference statements)
3
141
0
Order By: Relevance
“…Recent demonstrations and theoretical predictions showed that such WR actuation could be extremely powerful and efficient, [7][8][9] inspiring the growing studies and development of WR structures for actuators and artificial muscles. [10][11][12][13][14][15][16][17] Notable WR examples include a titanium oxide film [18] and a twisted carbon nanotube yarn, [19] which exhibit WR energy densities of ≈1250 and 1800 kJ m −3 (2.17 kJ kg −1 ), respectively. Microrobots equipped with WR actuators of 𝜋-stacked carbon nitride films [8] and polyethylene oxide nanofibers [20] have been demonstrated to exhibit autonomous locomotion powered by fluctuations in ambient RH.…”
Section: Doi: 101002/advs202104697mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent demonstrations and theoretical predictions showed that such WR actuation could be extremely powerful and efficient, [7][8][9] inspiring the growing studies and development of WR structures for actuators and artificial muscles. [10][11][12][13][14][15][16][17] Notable WR examples include a titanium oxide film [18] and a twisted carbon nanotube yarn, [19] which exhibit WR energy densities of ≈1250 and 1800 kJ m −3 (2.17 kJ kg −1 ), respectively. Microrobots equipped with WR actuators of 𝜋-stacked carbon nitride films [8] and polyethylene oxide nanofibers [20] have been demonstrated to exhibit autonomous locomotion powered by fluctuations in ambient RH.…”
Section: Doi: 101002/advs202104697mentioning
confidence: 99%
“…Recent demonstrations and theoretical predictions showed that such WR actuation could be extremely powerful and efficient, [ 7 , 8 , 9 ] inspiring the growing studies and development of WR structures for actuators and artificial muscles. [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…g) Comparison of the electrical conductivity and tensile strength between MAF‐0.25 and previously reported MXene‐based films. [ 14,16,23,25,27,28,31,35,38,44,48–53 ]…”
Section: Resultsmentioning
confidence: 99%
“…Hence, the excellent long-term stability of AMP3-based sensor was confirmed, which could be attributed to the tight bonding of the PDA layer with the surface of the AMX sheet and cut off the path of oxygen permeation. 35 The response and recovery times of the AMP3-based sensor were obtained by fastly moving the sensor from atmospheric environment (∼40% RH) into the humidity chamber (∼95% RH); the obtained values were 0.4 s and 0.5 s, respectively (see Fig. 2(e) and Fig.…”
Section: Resultsmentioning
confidence: 99%